Convergence analysis of an iterative algorithm to solve system of nonlinear stochastic Itô‐Volterra integral equations - Saffarzadeh, Masoud; Heydari, Mohammad; Barid Loghmani, Ghasem (Mathematical methods in the applied sciences, 2020)
In this paper, an efficient and accurate numerical iterative algorithm based on the linear spline interpolation for solving the system of nonlinear stochastic Itô‐Volterra integral equations is presented. The most important merit of this method is that it does not need to solve any system of nonlinear algebraic equations. An upper bound for the linear spline approximation of the stochastic function is provided. Using this upper bound and under the Lipschitz and linear growth conditions, the convergence analysis of the suggested method is studied. Finally, to verify the efficiency of the proposed scheme, some problems in the finance, physics, and biology are investigated, and the obtained results are compared with the stochastic θ‐method.